Exciter Jammer Berbasis Direct Digital Synthesizer - Elan Djaelani Suardja; Purwoko Adhi (INKOM Journal, 2013)
In this paper, we propose a radio transmitter jamming device modification developed. The transmitter is built by replacing Voltage Controled Oscillator (VCO) with modules for Direct Digital Synthesizer (DDS) as an exciter. Advantages of DDS is programmed with a computer and can produce a signal with a frequency stability and frequency accuracy is very high. The use of DDS allow setting the frequency of central and deviation with very easily using software. In addition, the period or sweep time designed to use only software can be reprogrammed with DDS to function on a Linear Sweep No Dwell mode and signaltrigger with a period equal to the period the minimum desired sweep. DDS allows to generate a signal jamming by narrow BW, so the power output of the Jammer could be higher and increased outreach of radio jamming. Another advantage with theuse of DDS is the dimension transmitter Jammer becomes smaller.keywords: Jamming devices, DDS, Eletronics warfare Pada tulisan ini, modifikasi perangkat pemancar radio jamming diusulkan, dengan mengganti Voltage Controled Oscilator (VCO) dengan modul Direct Digital Synthesizer (DDS) sebagai exciter. Kelebihan DDS adalah bisa diprogram dengan komputer dan menghasilkan sinyal dengan stabilitas dan akurasi frekuensi yang sangat tinggi. Penggunaan DDS memungkinkan pengaturan frekuensi tengah dan deviasi dengan sangat mudah menggunakan sofware. Di samping itu, periode atau waktu sweep dirancang untuk bisa diatur hanya menggunakan software dengan memprogram DDS untuk berfungsi pada mode Linear Sweep No Dwell dan memberikan sinyal trigger dengan periode sebesar periode sweep minimum yang diinginkan. DDS memungkinkan untuk menghasilkan sinyal jamming dengn BW yang sempit, sehingga power output Jammer bisa lebih tinggi dan daya jangkau radio jamming meningkat. Keuntungan lain dengan penggunaan DDS adalah dimensi pemancar Jammer menjadi lebih kecil.kata kunci: Perangkat Jamming, DDS, Perang elektronik